Un Encàrrec de l'infant Pere d'Aragó i d'Anjou a Ferrer Bassa el 1346: el Saltiri anglocatalà - Martínez Elcacho, Albert (Miscel·lània litúrgica catalana, 2016)
This paper presents some unpublished documents related to an illuminated manuscript which was illustrated in Catalonia in the 14th century. The patron of this artwork was a member of the royal family, Infante Peter of Aragon and Anjou, and the artist who executed it was the painter Ferrer Bassa. In particular, the book to be illuminated was an already written, glossed and historiated psalter to which some scenes had to be added. The illumination was done between the end of 1346 and mid-1348. Based on these premises and other arguments, we identify the artwork in question as the Great Canterbury Psalter (Anglo-Catalan Psalter), which is housed in the Biblio- thèque Nationale de France (Manuscrit Latin 8846) in Paris. This confirms the authorship of the artwork and sets its execution chronologically. Until now, the attribution and dating of the mi- niature illustrations had varied according to the different published studies. In addition, this study shows that the artwork patron is an unexpected one, Infante Peter of Aragon, a crucial person to understand the 14th century from the Catalan and European perspectives.